Exchange rate pass-through in the global economy: the role of emerging market economies - Matthieu Bussière; Tuomas A. Peltonen (European Central Bank (ECB), 2008)
This paper estimates export and import price equations for 41 countries –including 28 emerging market economies. Further, it relates the estimated elasticities to structural factors and tests for statistical breaks in the relation between trade prices and exchange rates. Results indicate that (i) the elasticity of trade prices in emerging markets is sizeable, but not significantly higher than in advanced economies; (ii) such elasticity is primarily influenced by macroeconomic factors such as the exchange rate regime and the inflationary environment, although microeconomic factors such as product differentiation also play a role; (iii) export and import price elasticities tend to be strongly correlated across countries; (iv) pass-through to import prices has declined in some advanced economies, noticeably the United States; this is consistent with a rise in pricing-to-market in several EMEs and especially with a change in the geographical composition of U.S. imports.
Keywords: F10; F30; F41; 330; Emerging market economies; Exchange Rate Pass-Through; exchange rate regime; local and producer currency pricing; pricing-to-market; Exchange Rate Pass-Through; Außenhandelspreis; Wechselkurssystem; Schwellenländer; Schwellenländer; Welt